Regulatory RNAs in Haloferax volcanii. (19th January 2011) - Fischer, Susan; Benz, Juliane; Späth, Bettina; Jellen-Ritter, Angelika; Heyer, Ruth; Dörr, Marcella; Maier, Lisa-Katharina; Menzel-Hobeck, Clemens; Lehr, Matthias; Jantzer, Katharina; Babski, Julia; Soppa, Jörg; et al.
Abstract : In organisms of all three domains of life, a plethora of sRNAs (small regulatory RNAs) exists in addition to the well-known RNAs such as rRNAs, tRNAs and mRNAs. Although sRNAs have been well studied in eukaryotes and in bacteria, the sRNA population in archaea has just recently been identified and only in a few archaeal species. In the present paper, we summarize our current knowledge about sRNAs and their function in the halophilic archaeon Haloferax volcanii . Using two different experimental approaches, 111 intergenic and 38 antisense sRNAs were identified, as well as 42 tRFs (tRNA-derived fragments). Observation of differential expression under various conditions suggests that these sRNAs might be active as regulators in gene expression like their bacterial and eukaryotic counterparts. The severe phenotypes observed upon deletion and overexpression of sRNA genes revealed that sRNAs are involved in, and important for, a variety of biological functions in H. volcanii and possibly other archaea. Investigation of the Haloferax Lsm protein suggests that this protein is involved in the archaeal sRNA pathway.